2019
DOI: 10.18332/tpc/102277
|View full text |Cite
|
Sign up to set email alerts
|

Response to Tobacco Free Ireland 2025: SimSmoke prediction for the end game

Abstract: Dear Editors, Li and colleagues are to be commended for their recent article 1 that uses the SimSmoke simulation model to predict that Ireland will fail to meet its target of being smoke free by 2025, which it defines as having a smoking rate of less than 5% 2. It is hoped that, despite the limitations inherent in any predictive computer modelling, their quantitative analysis of the forthcoming failure for Ireland to meet its own targets will spur the Irish Government into assertively tackling the tobacco epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Previous studies have found higher tobacco use rates in youth who identify as bisexual 8 , 14 , including increased risk in adolescent bisexual girls 7 , 12 , 14 and lesbians 7 , 12 , pointing to increased risk for usage and ultimately adverse health outcomes for sexual minority girls 15 . Although studies with youth sexual minority subpopulations are few, research with adults has reported that lesbians and bisexual women have greater odds of tobacco use 16 , including dual use 17 , with some research suggesting that bisexual women are particularly at risk 18 , 19 . However, this study is one of the first to report significantly greater odds of dual/poly tobacco use by female sexual minority youth.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found higher tobacco use rates in youth who identify as bisexual 8 , 14 , including increased risk in adolescent bisexual girls 7 , 12 , 14 and lesbians 7 , 12 , pointing to increased risk for usage and ultimately adverse health outcomes for sexual minority girls 15 . Although studies with youth sexual minority subpopulations are few, research with adults has reported that lesbians and bisexual women have greater odds of tobacco use 16 , including dual use 17 , with some research suggesting that bisexual women are particularly at risk 18 , 19 . However, this study is one of the first to report significantly greater odds of dual/poly tobacco use by female sexual minority youth.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking continues to extract an unacceptably high toll in Ireland in terms of both mortality and morbidity, as well as through its financial burden 1 . Despite recent declines in smoking rates in Ireland 2 , the 2025 target of a smoking rate of less than 5%, which would make Ireland in its government's eyes 'smoke-free' 3 , appears decades 4 , or more 5 , away. Recent evidence suggests an overall adult smoking rate of 17% in Ireland, with a male rate of 19% and a female rate of 16%.…”
Section: Introductionmentioning
confidence: 99%
“…Some other pathologies frequently linked to tobacco use are oral candidiasis, palatal nicotinic stomatitis and the so-called ‘smoker's melanosis’. Compared to smokers of conventional cigarettes, smokers of e-cigarettes present a higher rate of nicotine stomatitis, hyperplastic candidiasis and ‘black hairy’ tongue 3 - 8 . The precancerous lesions found in smokers should also be mentioned.…”
mentioning
confidence: 99%